Soil moisture dynamics and evapotranspiration water consumption in spring maize (Bangladesh Journal of Botany, 2023)
In the present study the dynamics of soil reservoir and evapotranspiration in dry farmland were thoroughly analyzed based on the long-term positioning test and investigation of soil moisture dynamic changes of spring maize. It was found that the vertical distribution curve of annual average soil water content in spring maize field was “single peak and single valley” type. Compared with wet (high water) years, the regulation depth of soil reservoir in the field during the growth period of Spring Maize in dry years moved up and becomes shallow; The soil moisture of Spring Maize in dry (low water) years was more stable than that in wet years. Under the two precipitation years, the “water level” of soil reservoir showed the characteristics of first rising, then falling, and then rising patterns. This study clarified the water source of evapotranspiration water consumption during the growth period of spring maize, evaluated the water balance of farmland ecosystem, and a preliminary understanding of the formation and restoration process of soil dry layer, which provided data support and theoretical basis for improving the practice of existing knowledge of production practice and sustainable development of dry farming.Bangladesh J. Bot. 52(2): 473-478, 2023 (June) Special